Temporally distinct regulation of pathways contributing to cardiac proteostasis during the acute and recovery phases of sepsis - Crowell, Kristen T. (Shock, 2018)
BACKGROUND: Cardiac dysfunction is a common manifestation of sepsis and is associated with early increases in inflammation and decreases in myocardial protein synthesis. However, little is known regarding the molecular mechanisms regulating protein homeostasis during the recovery phase after the removal of the septic nidus. Therefore, the purpose of this study was to investigate diverse signal transduction pathways that regulate myocardial protein synthesis and degradation. METHODS: Adult male C57BL/6 mice were used to identify potential mechanisms mediating the acute (24 h) effect of cecal ligation and puncture (CLP) as well as long-term changes that manifest during the chronic (10 d) recovery phase. RESULTS: Acutely, sepsis decreased cardiac protein synthesis that was associated with reduced phosphorylation of S6K1/S6 but not 4E-BP1. Sepsis also decreased proteasome activity, although with no change in MuRF1 and atrogin-1 mRNA expression. Sepsis acutely increased apoptosis (increased caspase-3 and PARP cleavage), autophagosome formation (increased LC3B-II), and canonical inflammasome activity (increased NLRP3, TMS1, cleaved caspase-1). In contrast, during the recovery phase, independent of a difference in food consumption, global protein synthesis was increased, the early repression in proteasome activity was restored to basal levels, while stimulation of apoptosis, autophagosome formation and the canonical inflammasome pathway had abated. However, during recovery there was a selective stimulation of the non-canonical inflammasome pathway as evidenced by activation of caspase-11 with cleavage of Gasdermin D. CONCLUSION: These data demonstrate a temporally distinct homeostatic shift in the cardiac proteostatic response to acute infection and recovery.